Prioritizing Health: The Need for Comprehensive Maternal and Child Care in Pakistan - Rana, Saleem Muhammad (Pakistan Journal of Health Sciences, 2024)
Pakistan grapples with severe maternal and child health challenges, highlighted by persistently high mortality rates that reveal significant shortcomings in the healthcare system. Over 90% of deaths among children aged five and younger occur in just 40 countries, primarily in South Asia and Sub-Saharan Africa. Pakistan, is a young and densely populated nation with a population of 240,485,658 as of 2023, with 13.21% of its population under the age of five [1]. The country ranks third in the world for newborn mortality and second for stillbirth rates. The relationship between poverty and maternal and child mortality in Pakistan is complex, with a weak healthcare system being a significant contributing factor. Under nutrition is an important factor and has a close link with child mortality. Addressing these health disparities is crucial for improving outcomes for mothers and children in the country. One of the primary reasons for poor health outcomes in Pakistan is the low priority assigned to the health sector by successive governments. A recent survey indicates that only 0.05% of the GDP was allocated to national health accounts. Data from Demographic and Health Surveys indicate a notable increase in awareness and access to healthcare for pregnant women, as well as for children suffering from illnesses like diarrhea and pneumonia. However, these improvements still fall short when compared to developed countries. Pakistan failed to meet the targets for infant and maternal mortality outlined in the Millennium Development Goals. Utilizing a trained healthcare professional instead of an untrained traditional birth attendant (DAI) or a family member for maternal and child health services, particularly for prenatal care and birth attendance, is essential and plays a critical role in ensuring maternal health. Women who have access to healthcare services tend to experience healthier pregnancies and give birth to healthier infants. In countries with robust healthcare systems and heightened awareness, maternal health is prioritized, enabling women to receive quality care during pregnancy and childbirth. An observational study was conducted to explore ways to reduce mortality rates, revealing that significant improvements could be achieved through the implementation of evidence-based care packages provided by available healthcare providers. Implementing primary and secondary care interventions could save nearly two-thirds of newborn and maternal lives. It is crucial to introduce these interventions in community settings, particularly in rural and hard-to-reach populations. These communities urgently require community-based platforms that facilitate problem recognition and referrals for care. The Lady Health Worker Programme is one of the largest initiatives globally and has significant potential to improve Reproductive, Maternal, Newborn, Child, and Adolescent Health. However, this potential can only be realized if access, quality of care, and appropriate referrals to functional facilities are ensured.